Dari Bantuan Menjadi Harapan: Pendampingan Penyaluran Dana Bantuan Sosial di Kantor Pos Bangkalan - Barokatus Syafaa; Atik Emilia Sula (Senarai Kearifan Lokal Akuntansi: Jurnal Pengabdian Masyarakat, 2026)
PT Pos Indonesia acts as a partner in distributing bansos to the community. One of the problems faced by partners in the social assistance distribution process is the high number of recipients arriving simultaneously, potentially causing long queues, service delays, and disorder in the distribution process. This community service activity was carried out through assistance assistance distribution at the Bangkalan Post Office with the aim of helping smooth services, starting from recipient data verification, queue management, to the aid disbursement process. The methods used included observation, field assistance, and coordination with distribution officers. The results of the activity showed that assistance was able to support smooth distribution to 171 beneficiaries out of a total of 175 registered recipients. This activity has an impact on creating a more orderly, targeted, smooth distribution process, and increasing community comfort in receiving social assistance.